Correlates of transient versus persistent psychotic symptoms among dependent methamphetamine users. (30th April 2016) - McKetin, Rebecca; Gardner, Jonathon; Baker, Amanda L.; Dawe, Sharon; Ali, Robert; Voce, Alexandra; Leach, Liana S.; Lubman, Dan I.
Abstract: This study examined correlates of transient versus persistent psychotic symptoms among people dependent on methamphetamine. A longitudinal prospective cohort study of dependent methamphetamine users who did not meet DSM-IV criteria for lifetime schizophrenia or mania. Four non-contiguous one-month observation periods were used to identify participants who had a) no psychotic symptoms, (n=110); (b) psychotic symptoms only when using methamphetamine (transient psychotic symptoms, n=85); and, (c) psychotic symptoms both when using methamphetamine and when abstaining from methamphetamine (persistent psychotic symptoms, n=37). Psychotic symptoms were defined as a score of 4 or greater on any of the Brief Psychiatric Rating Scale items of suspiciousness, hallucinations or unusual thought content. Relative no psychotic symptoms, both transient and persistent psychotic symptoms were associated with childhood conduct disorder and comorbid anxiety disorders. Earlier onset methamphetamine use and being male were more specifically related to transient psychotic symptoms, while a family history of a primary psychotic disorder and comorbid major depression were specifically related to persistent psychotic symptoms. We conclude that there are overlapping but also distinct clinical correlates of transient versus persistent psychotic symptoms, suggesting potentially heterogeneous etiological pathways underpinning the psychotic phenomena seen amongst people who use methamphetamine. Highlights: Correlates of transient and persistent psychotic symptoms in methamphetamine users differ. Earlier onset methamphetamine use and being male predict transient psychosis. Major depression and family history of schizophrenia predict persistent psychosis. Anxiety disorders and conduct disorder predict both transient and persistent psychosis.